Toleransi Tanaman Peneduh Polyalthia longifolia dan Pterocarpus indicus terhadap Ganoderma sp. - Siti Muslimah Widyastuti; Harjono .; I Riastiwi (Universitas Lampung, 2013)
Susceptibility of Urban Trees Polyalthia longifolia and Pterocarpus indicus to Infection of the red root rot fungus Ganoderma sp. Urban trees on the Gadjah Mada University (UGM) area play an important role in increasing environmental qualities as well as in supporting the teaching and learning processes. However, red root rot disease caused by Basidiomycete Ganoderma sp. has severely infected some existing urban trees. This experiment was aimed to determine the susceptibility of Polyalthia longifolia (glodokan) and Pterocarpus indicus (angsana) to the infection of Ganoderma sp. Identification of infected trees was performed in UGM area. Further steps were carried out to achieve those objectives : (1) isolation of Ganoderma spp. and testing of Koch’s postulate and (2) examination of the susceptibility of P. longifolia and P. indicus to infection of Ganoderma sp. The susceptibility test of P. longifolia and P. indicus to Ganoderma sp. indicated that P. longifolia was more resistant to fungal pathogen infection than that of P. indicus. Based on this experiment, it can be concluded that P. longifolia is a species that is more suitable than P. indicus. P. longifolia should be planted on the areas that have been infested with inocula of Ganoderma sp..